Paul Krugman: Kontribusi dan Kontroversinya - Panennungi, Maddaremmeng A. (UI Scholars Hub, 2010)
This study isaimed toinvestigate the contribution and controversies of Nobel Prize Winner in Economics in 2008, Paul R. Krugman, in economics field and in the society as a whole. Literature survey method isapplied in thisstudy. It isfound that the Krugman's contribution in theinternational trade is substantial for the development of international trade theory. He is also contributing to development of economic geography. In addition, his contribution to the international finance is also very important eventhough it is not recognized by the Nobel Committee. Out of the economic fields as his main contribution is his capability in bringing the economics into public discussion in both popular writings and public discussion or seminar is also admirable. Another side of Krugman is that his strong opinion sometimes creates controversies in both good and bad ways.